Factors associated with stress-related symptoms among people with epilepsy in Ethiopia, a cross-sectional study - Seid, Jemal; Gebrehiwot, Birhane; Andualem, Fantahun; Kassaye, Abenet; Mohammed, Jemal; Akele, Mulugeta (Frontiers in Neurology, 2023)
Introduction Stress is a common psychological problem present in people with epilepsy and has a serious impact on the health-related satisfaction of people with epilepsy and their cohabiters. This study aimed to assess the magnitude and related factors of stress. Methods A hospital-based cross-sectional study was carried out among 301 systematically chosen people with epilepsy. The seven stress-related items of the Depression, Anxiety, and Stress -21 questionnaire was used to measure stress. Data were entered using Epi Info and analyzed by SPSS version 25. Predictors with a p-value < 0.20 in the bivariate logistic regression were transferred into the multivariate model. A p-value of less than 0.05 was viewed as statistically significant. Result The prevalence of stress symptoms in this study was 23.9%. Daily labor occupational status with Adjusted Odds ratio [(AOR) = 0.042, 95% CI: 0.004, 0.469], onset of illness at the age of 18 years and above (AOR = 0.188, 95% CI: 0.046, 0.771), perceived stigma (AOR = 3.320, 95% CI: 1.345, 8.200), the presence of anxiety symptoms (AOR = 8.275, 95% CI: 3.345, 20.471), and belief that the condition is untreatable (AOR = 6.360, 95% CI: 1.647, 24.562) were significantly associated factors. Conclusion The occurrence of stress was high, and it reinforced that there is a requisite for the identification and handling of stress-related symptoms among people with epilepsy.